PERANCANGAN SISTEM INFORMASI PEMESANAN INTERIOR PADA PT CIPTA KREASI BUANA BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE - Sabrina Hasyati; Syarifah Syarifah; Ranggi Ramdani; Eril Miso; Arif Kusnandar (CV. Denasya Smart Publisher, 2025)
This study aims to design a web-based interior ordering information system for PT Cipta Kreasi Buana, which has been operating since 2015. Currently, the process of ordering products and interior services is still conducted manually, which can lead to errors in order writing and a lack of transparency for customers. The method used in this research is the prototype method, which includes needs analysis, system design, application development, and evaluation. The primary focus of this system design is to create an intuitive and responsive user interface, making it easier for customers to place orders. The results of this study indicate that the implementation of the web-based ordering information system can enhance the efficiency and effectiveness of the company's operations. The designed application allows customers to place orders more easily and quickly, while also providing better management of orders and inventory. With this system in place, PT Cipta Kreasi Buana can improve customer satisfaction and keep up with digital technology advancements. This research is expected to serve as a reference for other companies in developing similar information systems.